Kilka refleksji o Rashomonie - Hendrykowski, Marek (Przestrzenie Teorii, 2019)
Hendrykowski Marek, Kilka refleksji o Rashomonie [A few Reflections on Rashomon]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 129–141. ISSN 1644-6763. DOI 10.14746/pt.2019.32.6. A masterpiece of Japanese and world cinema, Akira Kurosawa’s Rashomon (1950) refers to a new model of narration in film, and broadens horizons in mid-20th-century film but also film in current imes. Rashomon set out new paths and fields of exploration in film art and began a new era in modern narration in moving pictures. This study re-evaluates Kurosawa’s work as an innovative, trans-national and trans-cultural approach to world cinema.